The Influence of Profitability and Liquidity on Tax Aggressiveness (Empirical Evidence from Manufacturing Companies Listed on the Indonesia Stock Exchange in 2019–2023) - Febriyanti, Shilla; Arifin, Arifin (Jurnal Ekonomi, 2025)
This study aims to examine the effect of profitability and liquidity on tax aggressiveness in food and beverage manufacturing companies listed on the Indonesia Stock Exchange. A quantitative approach was employed using secondary data obtained from the companies' annual financial reports during the observation period. Hypotheses were tested using multiple linear regression analysis with the assistance of EViews software. The findings reveal that profitability has a negative and significant effect on tax aggressiveness, indicating that higher profitability is associated with lower levels of tax aggressiveness. On the other hand, liquidity shows no significant effect on tax aggressiveness. Simultaneously, both profitability and liquidity have a collective influence on tax aggressiveness. These results provide valuable insights for corporate management in developing transparent financial strategies that align with sustainable tax compliance practices, and highlight the importance of internal financial performance in shaping ethical tax behavior.